2013
DOI: 10.1148/radiol.12120495
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Liver Metastasis Treated by Using Intraarterial Therapy: Volumetric Functional Imaging Biomarkers of Early Tumor Response and Survival

Abstract: Purpose To determine if volumetric changes of diffusion-weighted and contrast material–enhanced magnetic resonance (MR) imaging can help assess early tumor response to intraarterial therapy (IAT) in neuroendocrine liver metastasis (NELM). Materials and Methods This retrospective single-center comprehensive imaging analysis was performed in compliance with HIPAA and was institutional review board approved. Informed patient consent was waived. Seventy-one patients (39 men; mean age, 62.3 years) with NELM treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 33 publications
5
59
0
Order By: Relevance
“…Results from their studies suggest that ADC is an earlier surrogate of response compared to size criteria [6]. A survival benefit was demonstrated in cholangiocarcinoma treated by TACE and in neuroendocrine liver metastases treated by intraarterial therapy exhibiting response by ADC [10,11]. One of their study focused on the identification of volumetric functional response criteria of unresectable HCC treated by intraarterial therapy and confirmed that 3D ADC parameters permit to stratify survival [16].…”
Section: D Adcmentioning
confidence: 87%
See 1 more Smart Citation
“…Results from their studies suggest that ADC is an earlier surrogate of response compared to size criteria [6]. A survival benefit was demonstrated in cholangiocarcinoma treated by TACE and in neuroendocrine liver metastases treated by intraarterial therapy exhibiting response by ADC [10,11]. One of their study focused on the identification of volumetric functional response criteria of unresectable HCC treated by intraarterial therapy and confirmed that 3D ADC parameters permit to stratify survival [16].…”
Section: D Adcmentioning
confidence: 87%
“…In addition, volumetric delineation may replace uni/bidimensional measurements as imaging software and spatial resolution of imaging modalities evolve [2,8,9]. Beyond conventional mean apparent diffusion coefficient (ADC), volumetric ADC measurement provides more realistic tumor delineation compared to uni-or bi-dimensional approaches, and permits analyzing tumor response heterogeneity by generating histograms from voxel-by-voxel ADC values calculation [10][11][12]. The aim of the present study was to correlate changes in different anatomical (RECIST, anatomical volume), enhancement (mRE-CIST), and DWI parameters with post-transplant pathological analysis, and to discuss the added value of mRECIST and volumetric DWI combination for the response assessment of HCC after 90 Yttrium radioembolization (Y90).…”
mentioning
confidence: 99%
“…However, volumetric enhancement was unable to provide similar results, likely because cholangiocarcinoma is a relatively hypovascular tumour [16]. Finally, in patients with hepatocellular carcinoma and neuroendocrine tumour liver metastasis, both volumetric ADC and enhancement proved adequate in differentiating responders from non-responders, with a significant survival benefit for the responders [17, 18, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…Lipiodol uptake is a biomarker of response with CT; however, its strong radio-opacity may render difficult the evaluation of small foci of enhancement. MRI is the most sensitive cross-sectional imaging technique for depiction of endocrine tumor liver metastases (14,15) and can predict early tumor response to TACE with the help of volumetric imaging, where a 25% or greater decrease in arterial enhancement or 50% or greater decrease in venous enhancement correlate with better prognosis (16). The best imaging technique to monitor response after RE is still debated, with morphological response occurring often several months later than with other techniques (17,18).…”
Section: Contraindicationsmentioning
confidence: 99%